The Existence of Predatory Insects in the Agroecosystem of Potato Plant (Solanum tuberosum L.) Integrated with Refugia Plants - M Sarjan; Ruth Stella Petrunella Thei; Moh. Taufik Fauzi; Kisman Kisman; Aena Haviana (Pascasarjana, Mataram University, 2023)
Inappropriate handling of pests can cause substantial losses in both quantity and quality of potato plants. One of the promising alternative methods is by modifying the agroecosystem such as using refugia plants to conserve the diversity of predators in potato plants. This study aimed to determine the effect of refugia plants on the diversity of predatory insects in potato plants. This study used a randomized block design (RBD) with 6 treatments and 3 replications. Sampling of predatory insects was carried out using traps, namely the yellow pan trap and direct (conventional) collection. The results of this study indicated that there were 3 orders of predatory insects from 3 families and 9 species. The most common insects were found in the treatment of marigold and sunflower flowers. The highest diversity index value was 1.33 obtained in the sunflower treatment, which is classified as moderate